Sulfur and nitrogen co-doped graphene for metal-free catalytic oxidation reactions - Duan, X.; O'Donnell, Kane; Sun, Hongqi; Wang, Yuxian; Wang, Shaobin (Wiley, 2015)
Sulfur and nitrogen co-doped reduced graphene oxide (rGO) is synthesized bya facile method and demonstrated remarkably enhanced activities in metal-free activation of peroxymonosulfate (PMS) for catalytic oxidation of phenol. Based on first-order kinetic model, S–N co-doped rGO (SNG) presents an apparent reaction rate constant of 0.043 ± 0.002 min -1 , which is 86.6, 22.8, 19.7, and 4.5-fold as high as that over graphene oxide (GO), rGO, S-doped rGO (S-rGO), and N-doped rGO(N-rGO), respectively. A variety of characterization techniques and density functional theory calculations are employed to investigate the synergistic effect of sulfur and nitrogen co-doping. Co-doping of rGO at an optimal sulfur loading can effectively break the inertness of carbon systems, activate the sp 2 -hybridized carbon lattice and facilitate the electron transfer from covalent graphene sheets for PMS activation. Moreover, both electron paramagnetic resonance (EPR) spectroscopy and classical quenching tests are employed to investigate the generation and evolution of reactive radicals on the SNG sample for phenol catalytic oxidation. This study presents anovel metal-free catalyst for green remediation of organic pollutants in water.